Clinical Significance of Applause Sign in Patients with Progressive Supranuclear Palsy. (13th November 2022) - Chatterjee, Koustav; Choudhury, Supriyo; Trivedi, Santosh; Basu, Purba; Kumar, Hrishikesh
ABSTRACT: Applause sign (AS) is a clinical phenomenon observed in several neurological disorders including progressive supranuclear palsy (PSP). We investigated the factors associated with AS in patients with PSP. PSP patients with AS showed greater motor impairment compared to those with negative AS. Global cognition including attention and memory were affected more in patients with positive AS. We also observed that gait variability, a known marker for unstable gait is pronounced in those who presented with positive AS. Hence, the clinician might expect a more severe disease and an unstable gait in a PSP patient presenting with AS.